Central banks' voting records and future policy - Roman Horváth; Kateřina Šmídková; Jan Zápal (Charles University in Prague, Institute of Economic Studies (IES), 2011)
We assess whether the voting records of central bank boards are informative about future monetary policy. First, we specify a theoretical model of central bank board decision-making and simulate the voting outcomes. Three different versions of model are estimated with simulated data: 1) democratic, 2) consensual and 3) opportunistic. These versions differ in the degree of informational influence between the chairman and other board members influence prior to the voting. The model shows that the voting pattern is informative about future monetary policy provided that the signals about the optimal policy rate are noisy and that there is sufficient independence in voting across the board members, which is in line with the democratic version. Next, the model predictions are tested on real data on five inflation targeting countries (the Czech Republic, Hungary, Poland, Sweden and the United Kingdom). Subject to various sensitivity tests, it is found that the democratic version of the model corresponds best to the real data and that in all countries the voting records are informative about future monetary policy, making a case for publishing the records.
Keywords: C78; D78; E52; E58; 330; monetary policy; voting record; transparency; collective decisionmaking; Geldpolitik; Zentralbank; Gruppenentscheidung; Prognoseverfahren; Inflationssteuerung; Tschechische Republik; Ungarn; Polen; Schweden; Großbritannien